The Role Of Da’i In Religious Guidance To The People Of Acheh’s Border And Remote Areas - Asmadin Asmadin; Silvianetri Silvianetri; Syafrizal Syafrizal (Jurnal Masyarakat Religius dan Berwawasan, 2022)
This paper is the result of da I service in borders and remote Aceh to carry out religious guidance to the community so that it is always maintained aqidah umat The approach taken in this study is Participatory Action Research par A service-based research The purpose of PAR is to understand the community in a certain area As for the steps of PAR research through 1 Initial mapping 2 Building Trust Relationships with the Community 3 Designing a Service Agenda 4 Participatory mapping in community groups 5 formulating problems experienced through tree analysis of problems 6 determining the parties involved stakeholders and formulating the possible successes and failures of the planned program and finding solutions if there are obstacles that hinder the success of the program 7. community organizing 8. Carrying out change actions service activities 9. Building a community learning center  are carried out through mentoring the implementation of religious guidance activities throught pioneering activities of Islamic boarding schools activating parentalrecitation to carry out guidance in anticipation of apostasy to increase the understanding of Islamic teaching as a whole fostering and strengthening the creed of the ummat teaching and guiding reading  the quran and fostering a quran education garden motivating the community to improve the quality of religious practice and always doing silaturrahmi to res idents